Consumer Satisfaction in Shopping Mall: A Sociological study in context of shopping mall attributes - Misra, Pawan Kumar; verma, Aayushi (South Asian Journal of Social Sciences and Humanities, 2023)
The purpose of this study is to investigate the effect of mall attributes on tourist satisfaction and behavioral intentions. To see what types of people are most likely to visit shopping malls, we studied the different demographic profiles of society. Shopping is often the most important domestic income-generating leisure activity. Driven by an increase in tourism in the country, today's shopping activity is more than just spending money on souvenirs and merchandise purchases in exchange for travelers getting a unique experience. Therefore, in this study, further, we try to understand the different visiting purposes of different profiles of tourists.A better understanding of shopping mall attributes in predicting tourist shopping satisfaction is critical to the success and sustainability of the shopping tourism industry. Mall managers and retailers may find it helpful to encourage repurchase intention, loyalty, and desire to stay longer at the shopping malls by providing attractive and convenient shopping experiences.
Keywords: Shopping mall; purpose of visit; shopping mall attributes; consumer satisfaction